Modeling of initial and final correlation effects in double ionization of noble gases and methane: contribution of the second born term - SAKHRAOUI , Wafa; KADA , Imene Supervisor (Setif 1 University - Ferhat ABBAS , Faculty of Sciences, 2025)
This thesis investigates the double ionization of atoms and molecules by electron impact, a key process to understanding particle-matter interactions. After introducing the fundamentals of scattering theory and cross-section concepts, the study focuses on double ionization mechanisms (shake-off, two-step 1, and two-step 2), emphasizing the critical role of electron correlation. Several theoretical models, including BBK (3C), DWBA, and 2CWG, are employed to describe the final-state electron dynamics. Applications to atomic (Neon, Krypton) and molecular (CH₄) targets demonstrate good agreement with experimental data, especially when correlation and distortion effects are included, validating the theoretical approach
Cette thèse traite de l’ionisation double des atomes et molécules par impact électronique, un processus fondamental dans la compréhension des interactions particules-matière. Après avoir introduit la théorie de la diffusion et les concepts de sections efficaces, l’étude explore les mécanismes d’ionisation double (shake-off, two-step 1 et two-step 2) en mettant en évidence l’importance des corrélations électroniques. Divers modèles théoriques, tels que BBK (3C), DWBA et 2CWG, sont utilisés pour simuler ces processus. Les résultats obtenus pour des cibles atomiques (Néon, Krypton) et moléculaires (CH₄) sont comparés à des données expérimentales et montrent que la prise en compte des effets de corrélation et de distorsion améliore significativement les prédictions théoriques